Penatalaksanaan Manajemen Nyeri Pada Ibu Bersalin - Rizal Nova Jalaludin; Erida Fadila; Dewi Oktoviani; Evi Nurmala Fia; Kiki Ameliya (MEJORA Medical Journal Awatara, 2024)
Pain and discomfort in pregnant women arise due to uterine contractions which are a physiological response to labor. The pain that arises after childbirth is the body's natural response to tissue damage during labor. Childbirth pain can be caused by uterine contractions, cervical dilatation, fetal expulsion or birth canal tears. As many as 99% of maternal deaths are caused by childbirth problems that occur in developing countries. Based on the problems and impacts caused, pain management is needed to reduce the pain. The purpose of this case study is to provide nursing care to G1P0A0 patients who experience labor pain. Using a qualitative approach with case studies as the main method, using observation sheets, interviews, and documentation studies. The case study selected 1 patient as the subject of study, namely a patient with G1P0A0 in the Maternal Emergency Room, RSUD Waled Cirebon. Nursing care management is based on the fulfillment of patient needs carried out in 1 day. The case study results indicate that after nursing care was provided, there was a reduction in pain levels. It is concluded that nursing care is effective for G1P0A0 patients experiencing labor pain, in meeting the patient's needs.